Mechanisms of Aletris spicata (Thunb.) Franch. Extract in Asthma Therapy: Oxidative Stress, Inflammation, and Gut Microbiota - Jing Yang; Zhiyong Chen; Yue Zhu; Teng Chen; Ying Zhou; Zuhua Wang (Biology, 2025)
Aletris spicata (Thunb.) Franch. (AS), a traditional edible and medicinal plant for treating asthma, was investigated for its therapeutic mechanisms. Liquid chromatography-high-resolution tandem mass spectrometry (LC-HRMS/MS) analysis identified 33 compounds in AS. In ovalbumin (OVA)-induced asthmatic mice, AS significantly reduced inflammatory cells (neutrophils, lymphocytes, eosinophils) in bronchoalveolar lavage fluid (BALF) and decreased IL-4, IL-5, IL-13, TNF-α, and serum IgE while increasing IFN-γ. AS alleviated lung and intestinal inflammation, reduced ROS and MDA levels, and enhanced SOD activity. Immunohistochemistry and Western blot revealed AS upregulated Nrf2/HO-1 expression and inhibited NF-κB p65 nuclear translocation. Gut microbiota studies demonstrated AS restored intestinal flora homeostasis by modulating the richness, diversity, and composition. Spearman correlation analysis identified significant relationships between oxidative stress markers, inflammatory cytokines, and specific gut bacteria. These findings indicate that AS mitigates asthma through antioxidant effects (Nrf2/HO-1 pathway), anti-inflammatory actions (NF-κB pathway), and gut microbiota modulation. The study provides a scientific basis for developing AS as a natural anti-asthma treatment or functional food. The multi-target mechanism involving oxidative stress, inflammation, and gut flora highlights AS’s comprehensive therapeutic potential for asthma management.